PROBLEMATIKA MANAJEMEN RISIKO DALAM MITIGASI TERORISME KELOMPOK FETO DI TURKI PADA MASA PRESIDEN ERDOGAN - Prastika, Mega; Impiani, Dwi (UI Scholars Hub, 2020)
This article aims to describe the new risks that emerged in mitigating the risk of FETO (Fethullah Gulen Terrorist Organization) in Turkey during President Erdogan's era. By having its own view of the state order and its strong network in 150 countries, the Gulen Movement is considered to threaten the existence of the ideology of the Turkish state, especially during the leadership of President Erdogan. After the failed coup attempt on July 15, 2016, the Gulen Movement was designated as a dangerous group called FETO as it was considered responsible for the incident. Furthermore, the Turkish government adopted an anti-terror policy that was preventive to repressive by implementing risk management in it. This article uses a qualitative method with data collection techniques in the form of literature studies which include: Official Document Based, and Internet Based Research. Using Selchow's (2014) four dynamics, this article finds that the actions taken by the Turkish government have an impact on the emergence of new problems and risks. These risks include the degradation of democracy and human rights violations, especially for Turkish citizens who are exposed to the “clean the state” agenda.